Етно-демографічна характеристика населення Північної Буковини і Хотинщини у міжвоєнний період - Rusnak, Oleksandr (Чернівці: Чернівецький нац. ун-т, 2019)
Стаття присвячена характеристиці етно-демографічної ситуації в Північній Буковині та на Хотинщині у період перебування у складі Румунії. Встановлено, що одним із позитивних наслідків можна вважати поступове збільшення загальної кількості населення досліджуваного регіону на 15,69%. Поряд із цим сповільненою була урбанізація. Хоч за міжвоєнний період кількість міського населення і збільшилася на 18,29%, проте співвідношення частки сільських і міських жителів суттєво не змінилося. Найвищі показники росту населення спостерігалися у Чернівцях (на 19,9%). Через відсутність достовірних матеріалів переписів не можливо визначити точний національний склад регіону. Натомість підтверджено те, що серед усіх національностей, що проживали у регіоні, переважаючу більшість складали українці.
The article deals with the characteristics of the ethno-demographic situation in Northern Bukovyna and Khotyn region during their stay in Romania. It was found that one of the positive effects can be considered a gradual increase in the total population of the studied region by 15,69%. At a time when Ukrainians were experiencing a number of demographic disasters, the Bukovyna-Bessarabian region recovered from the aftermath of World War I and demonstrated a qualitative population growth trend. Along with this slowdown was urbanization. Although in the interwar period the number of urban population increased by 18,29%, but the ratio of rural and urban residents did not change significantly. Migration processes from the village to the city, even if they took place, are hardly reflected in statistics. The highest rates of population growth were observed in Chernivtsi (by 19,9%). Due to the lack of reliable census materials, it is not possible to determine the exact national composition of the region. Instead, it is confirmed that among all the nationalities, who lived in Vashkivtsi, Vyzhnytsia, Zastavna, Kitsman, Storozhynets, Khotyn and Chernivtsi districts that existed before 1925, and in Storozhynets, Khotyn and Chernivtsi districts formed instead of them, Ukrainians were predominant.
Keywords: Північна Буковина, Хотинщина, населення, національний склад